Hydrochemistry of the lakes in the southern Badain Jaran Desert and its paleosalinity reconstruction - Gao-lei Jiang; Zhe Wang; Zhen-long Nie; Zhong-shuang Cheng; Pu-cheng Zhu; Le Cao; Jian-mei Shen (China Geology, 2024)
ABSTRACT: The reconstruction of paleohydrology, especially paleosalinity, is an important component of paleoenvironmental research. Researches on the modern characteristics of lake water chemistry and the relationship between lake salinity and hydrochemistry are the basis of paleoenvironment reconstruction. The modern hydrochemical characteristics and the relationship between ion composition and salinity of modern lakes are the basis of paleosalinity reconstruction. In this study, hydrochemical analysis of 21 lakes in the Badain Jaran Desert (BJD) was carried out. The relationships between the Sr/Ca and Mg/Ca ratios and total dissolved solids (TDS) were analyzed. The results show that Na+, K+, Cl− and SO42− have high positive correlations with TDS, and Mg2+, Sr2+, CO32− and HCO3− have lower correlations with TDS. The Sr/Ca and Mg/Ca ratios do not increase linearly with TDS. Hydrochemical analysis indicates that the studied lakes are in the carbonate precipitation stage and that evaporation is the main factor controlling lake evolution in the BJD. The relationships between the Mg/Ca and Sr/Ca ratios and TDS are mainly influenced by lake evolution stage and the hydrochemical types of the lakes. On the basis of comprehensive previous studies, the factors affecting lake evolution, the Mg and Sr partition coefficients and other hydrochemical parameters that change with lake evolution all affect the relationship between chemical composition and salinity. To reconstruct paleosalinity more accurately, more detailed research on the modern hydrochemical characteristics of lakes and the relationship between the element ratios of carbonates and water salinity should be carried out.